The Integration of Islamic Values in Person-Centered Group Counseling Theory and Practice: A Literature Review - Zerni, Eli; Darimis, Darimis (The Future of Education Journal, 2025)
The Person-Centered Therapy (PCT) approach developed by Carl R. Rogers emphasizes empathy, unconditional positive regard, and genuineness in the counseling process. Within Muslim society, this approach must be integrated with Islamic values so that counseling addresses not only psychological but also spiritual aspects. This literature review analyzes the theory and practice of person-centered group counseling integrated with Islamic principles. By reviewing literature from Rogers, Corey, Palmer, Al-Ghazali, and other scholars, it is found that Islamic integration in PCT emphasizes the balance between human potential (fitrah) and spiritual responsibility toward Allah SWT. Islamic-integrative group counseling serves as a means for individuals to recognize, accept, and develop themselves holistically—emotionally, socially, and spiritually. Values such as sincerity, compassion, repentance, and ukhuwah Islamiyah enrich the counseling process and help shape individuals who are psychologically healthy and spiritually mature.